THE USE OF METAPHORS IN ADVERTISEMENT OF COSMOPOLITAN MAGAZINE - Arina A. Panjaitan; Meisuri Meisuri (LINGUISTICA, 2012)
One aim of this article is to show through a concrete example how metaphors used in advertisement. The illustrative example is taken from the Cosmopolitan magazine. Central to the analysis of proper meanings of advertisement are the journalistic practices that contain the production of metaphor; i.e. the symbols, the words, or color of different values. Ten advertisements were interpreted by 103 students, and it was found that the use of symbols outnumbered the words, particularly those symbolized the nature. Keywords: advertisement; metaphor